Revisioning French culture - Sobanet, Andrew (Studies in modern and contemporary France., 2019)
Revisioning French Culture brings together a striking group of leading intellectuals and scholars to explore new avenues of research in French and Francophone Studies. Covering the medieval period through the twenty-first century, this volume presents investigations into a vast array of subjects, with global Francophonie as its primary focal point.